Characterization of Ex Vivo Expanded Oral Mucosal Epithelium Cells on Acellular Porcine Corneal Stroma for Ocular Surface Reconstruction. (8th May 2017) - Wang, Jia-Song; Xie, Hua-Tao; Zhang, Ming-Chang
Abstract : Purpose . To ex vivo expand oral mucosal epithelium cells (OMECs) on acellular porcine corneal stroma (APCS) without using feeder cells and serum and to compare the morphologic and phenotypic characteristics of cultured oral cells on APCS to those of cells on deluded human amniotic membrane (HAM). Methods . SD rat oral mucosal biopsies were cultured on APCS and HAM. Reverse-transcription polymerase chain reaction (RT-PCR) and immunohistochemistry were used to analyze the characterization of stem cells and epithelial differentiation of the outgrowth products. Results . Stratified and optimal transplantable OMECs were obtained after being cultured three to four weeks. Both RT-PCR and immunohistochemistry showed that cultured OMECs expressed markers of epithelial differentiation cytokeratin K3 and epithelial stem cell markers of p63 and ABCG2. Conclusions . OMECs can be successfully cultured on APCS without using xenobiotic feeder cells and serum. Characterization showed that these sheets retain the morphologic and phenotypic characteristics of OMECs within differentiated cells and stem cells. The optimal transplantable sheets can prove to be particularly beneficial to both bilateral limbal stem cell deficiency and deep corneal lesions.